THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH TO NON-PHILOLOGICAL STUDENTS.(CHEMISTRY) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the development of communicative competence in teaching English to non-philological students, specifically those specializing in Chemistry. It analyzes the unique linguistic challenges faced by chemistry students who require practical English skills for academic and professional communication within their scientific domain, such as effectively conveying scientific concepts, comprehending scientific texts, presenting research findings, and engaging in international collaboration. The paper discusses contemporary pedagogical approaches like English for Specific Purposes (ESP), content-based instruction, and task-based learning.